Strength and transport properties of steam cured and water cured lightweight aggregate concretes - Mermerdas, Kasim; Gesoglu, Mehmet; Guneyisi, Erhan; Ali, Barham (ELSEVIER SCI LTD, 2013)
In this paper, effect of steam and water curing on the compressive strength development and transport properties such as water sorptivity, rapid chloride ion permeability, and gas permeability of concretes containing various volumes of lightweight fly ash aggregate (LWA) were investigated. In production of concrete, a fixed amount of lightweight coarse (LWCA) aggregate plus varying amounts of lightweight fine aggregate (LWFA) were used. Utilization of LWFA was achieved by volumetric substitution of fine aggregate with five different replacement levels namely, 0%, 25%, 50%, 75%, and 100%. Therefore, five different concrete mixtures were produced for this experimental study. The produced concretes were divided into two parts one of which was initially steam cured while the other was directly exposed to water curing. After initial steam curing regime, the steam cured (SC) concretes were also transferred to water until testing Mechanical properties of concretes were monitored through compressive strength development over 56 days, while transport properties were measured by means of water sorptivity, gas permeability and rapid chloride permeability tests conducted at 28 and 56 days. Crown Copyright (C) 2013 Published by Elsevier Ltd. All rights reserved.
Keywords: Lightweight aggregate; Fly ash; Curing regime; Strength development; Transport properties